Effectiveness of Online Height Measurement Training for Parents - Fitri Yuniarti; Yenni Zuhairini; Fedri Ruluwedrata Rinawan (Faculty of Medicine Universitas Padjadjaran, 2022)
Background: The incidence of stunting in Indonesia is high (30.8%), therefore, regular monitoring of children’s height growth is needed. However, during the Covid-19 pandemic, the health service’s checks are limited, as well as schools as a potential place to monitor children’s growth are closed. This study aimed to assess the effectiveness of online height measurement training for parents.Methods: This was a quantitative research with one group pre-and post-intervention design. It was conducted in a rural area in West Java, from August to November 2021. The parents of school students were included with a purposive sampling method. The training media was in the form of height measurement videos. The assessment of parents’ skills was an online check sheet with a Likert scale of 1–5 using the Whatsapp application. Analyzes were performed with the Paired T-Test.Results: In total, 86 parents were included, all of whom were mothers with the majority (51.2%) age range of 36–45 year. Parental education varied with most elementary school graduates (27.9%). Most mothers did not work (59.3%). As for the students, the majority were female students (60.5%) between 6–9 years old. The skill score before and after training was effective (d=2.04; p=<0.001).Conclusion: Online height measurement training using video has high effectiveness in improving parents’ skills to self-practice measurement at home.